(untitled) (Revista Iberoamericana de Bioética, 2020)
The COVID-19 crisis has highlighted the precariousness and injustices within the healthcare systems of many African countries. Ever since the pandemic broke out on the continent, the ability of its health facilities to provide an adequate response to the COVID-19 crisis has been severely tested. Quality healthcare is a luxury that few can afford in Cameroon. Prevention and awareness campaigns are often the only means available to prevent the propagation of the virus. A return to herbal medicines appears to be the only way forward. This is a new field of research and therefore an invitation to a different approach to the ethics of life on the continent. Its exploration includes that which is specific to the continent; its proximity to nature and, as stated by Achille Mbembe, its rich ethics of travel.